x2-12x-13=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -13 and whose sum is -12.

-13,1

Write the factored form using these integers.

(x-13)(x+1)=0

(x-13)(x+1)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-13=0

x+1=0

Set the first factor equal to 0.

x-13=0

Add 13 to both sides of the equation.

x=13

x=13

Set the next factor equal to 0.

x+1=0

Subtract 1 from both sides of the equation.

x=-1

x=-1

The final solution is all the values that make (x-13)(x+1)=0 true.

x=13,-1

Solve using the Square Root Property x^2-12x-13=0